Genome mining to unravel potential metabolic pathways linked to gallium bioleaching ability of bacterial mine isolates - Chung, Ana Paula; Francisco, Romeu; Morais, Paula V.; Branco, Rita (Frontiers in Microbiology, 2022)
Gallium (Ga) is considered a high-tech Critical Metal, used in the manufacture of several microelectronic components containing either gallium arsenide (GaAs) or gallium nitride (GaN). The current high demand for this critical metal urges the development of effective recovery processes from secondary resources such as mine tailings or electronic recycling material. The importance of bioleaching as a biotechnological process to recover metals prompted this study, where an integrative approach combining experimental and genomic analysis was undertaken to identify potential mechanisms involved in bioleaching ability and strategies to cope with high metal(loid)s concentrations in five mine isolates. The Clusters of Orthologous Group (COG) annotation showed that the “amino acid transport and metabolism” [E] was the most predominant functional category in all genomes. In addition, the KEEG pathways analysis also showed predicted genes for the biosynthetic pathways of most amino acids, indicating that amino acids could have an important role in the Ga leaching mechanism. The presence of effective resistance mechanisms to Ga and arsenic (As) was particularly important in GaAs bioleaching batch assays, and might explain the divergence in bioleaching efficiency among the bacterial strains. Rhodanobacter sp. B2A1Ga4 and Sphingomonas sp. A2-49 with higher resistance, mainly to As, were the most efficient bioleaching strains under these conditions. In bioleaching assays using cell-free spent medium Arthrobacter silviterrae A2-55 with lower As resistance outperformed all the other stains. Overall, higher efficiency in Ga leaching was obtained in bioleaching assays using GaAs when compared to GaN.